1992
DOI: 10.1099/0022-1317-73-6-1481
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar expression of Autographa californica multiple nucleocapsid nuclear polyhedrosis virus polyhedrin and p10 genes

Abstract: The temporal expression of the Autographa californica multiple nucleocapsid nuclear polyhedrosis virus polyhedrin and p10 genes in Spodoptera frugiperda cells was studied using virus recombinants in which either gene was replaced by the juvenile hormone esterase (JHE) gene of Heliothis virescens. The JHE served as a highly specific and sensitive reporter for gene expression. Activation of the p10 gene followed a pattern different to that of polyhedrin. The p10 gene was activated a few hours earlier than the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 40 publications
1
33
1
Order By: Relevance
“…In the first of these studies expression of JHE under control of the pl0 promoter was consistently higher than expression under control of the polyhedrin promoter. In contrast, Roelvink et al (1992) found that the reverse was true for the pl0-negative virus at later times after infection.…”
Section: Introductioncontrasting
confidence: 41%
See 2 more Smart Citations
“…In the first of these studies expression of JHE under control of the pl0 promoter was consistently higher than expression under control of the polyhedrin promoter. In contrast, Roelvink et al (1992) found that the reverse was true for the pl0-negative virus at later times after infection.…”
Section: Introductioncontrasting
confidence: 41%
“…The coding sequence includes a 19 amino acid leader which signals export of expressed JHE from cells into the medium in cell culture. In vitro analysis of expression of JHE by recombinant viruses showed that the pl0 promoter is active several hours earlier than the polyhedrin promoter Roelvink et al, 1992). Conflicting results concerning the relative yields of JHE expressed under the control of the pl0 promoter in pl0-positive ) and pl0-negative (Roelvink et aL, 1992) viruses prompted further comparative analysis of these expression vectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,23,24 This is exacerbated for the viruses of the BAC/Tn7 type by the fact that the insertion site which is targeted by the Tn7 transposon is actually a mutational hotspot. 29,30 It is clear that the possibilities to improve the baculovirus itself are ample, and are far from exhausted in state of the art systems.…”
Section: Baculovirus Genome Engineeringmentioning
confidence: 99%
“…16 P10 gene is expressed a few hours before polyhedrin, thus leading to the overexpression of the H chains before the light chains and triggering of secretion of H chains dimers (H 2 ). 15 Since the correct folding of the heavy chain requires the presence of light chains, the unfolded H2 molecules may be at the origin of the formation of aggregates observed under these conditions. 17 Aggregation may in turn also explain the low expression rate observed in these conditions.…”
Section: Introductionmentioning
confidence: 99%